2003
DOI: 10.31899/hiv2.1043
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health services in KwaZulu Natal, South Africa: A situation analysis study focusing on HIV/AIDS services

Abstract: System, for their support of the research. We would also like to acknowledge all district managers and their management teams for their assistance and support throughout; the fieldworkers for their tireless effort; and all the facility management and staff for their assistance and participation during data collection. We would like to thank the Italian Health Cooperation for their financial contribution to make the study possible. Lastly we would like to thank the Maternal, Child & Women's Health Sub-Directora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Conversely, recent reports also describe the persistence of missed opportunities in service delivery, including failure to counsel FP clients on dual protection or con-dom use (Population Council 1999;Mayhew et al 2000;Adeokun et al 2002;Lafort et al 2003;Ndhlovu et al 2003;Maharaj and Cleland 2005); providers' preference for promoting injectable contraceptives over condoms (Ndhlovu et al 2003); their failure to conduct pelvic examinations (Chowdhury et al1999;Population Council 1999); and their failure to conduct behavioral risk assessments (Chowdhury et al 1999;Mayhew et al 2000;Lafort et al 2003), even in cases of clients who judge themselves to be at high risk (Maharaj and Cleland 2005). Studies suggest that these omissions are due to a variety of systemic shortcomings (among them, poor referral systems, too few staff, not enough time to offer all services, and training deficiencies) and also to factors such as providers' discomfort with talking about sexual health and their being poorly prepared and supported (Population Council 1999;Mayhew et al 2000).…”
Section: Uptake Of Servicesmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, recent reports also describe the persistence of missed opportunities in service delivery, including failure to counsel FP clients on dual protection or con-dom use (Population Council 1999;Mayhew et al 2000;Adeokun et al 2002;Lafort et al 2003;Ndhlovu et al 2003;Maharaj and Cleland 2005); providers' preference for promoting injectable contraceptives over condoms (Ndhlovu et al 2003); their failure to conduct pelvic examinations (Chowdhury et al1999;Population Council 1999); and their failure to conduct behavioral risk assessments (Chowdhury et al 1999;Mayhew et al 2000;Lafort et al 2003), even in cases of clients who judge themselves to be at high risk (Maharaj and Cleland 2005). Studies suggest that these omissions are due to a variety of systemic shortcomings (among them, poor referral systems, too few staff, not enough time to offer all services, and training deficiencies) and also to factors such as providers' discomfort with talking about sexual health and their being poorly prepared and supported (Population Council 1999;Mayhew et al 2000).…”
Section: Uptake Of Servicesmentioning
confidence: 99%
“…Moreover, evidence makes clear that integrated services can encourage the attendance and involvement of male partners, both for HIV testing (Mphuru et al 2006) and for STI treatment (Budiharsana 2002;Lafort et al 2003). Other studies from a range of SRH settings, however, found no increase in, or continuing low numbers of, male clients (Fullerton et al 2003;Ndhlovu et al 2003;EngenderHealth and UN-FPA 2006) and also found missed opportunities in cases where men attended in order to obtain STI care and were not offered FP services (Maharaj and Cleland 2005).…”
Section: Expansion Of Reach To Nontraditional Clientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some PLWH may also prefer specialized HIV care due to enacted provider stigma within SRH services [23, 24]. Furthermore, descriptive studies following service integration report that privacy is not always maintained in generalist settings, calling into question the supposed confidentiality of an integrated approach [17, 25, 26]. …”
Section: Introductionmentioning
confidence: 99%